The Role of Teachers and Parents in Overcoming Separation Anxiety in Early Childhood - Salbiyah, Siti; Pahrul, Yolanda; Nur, Maulida; Inten Risna; Ratu Yustika Rini (JURNAL PENA PAUD, 2026)
Separation Anxiety Disorder (SAD)   is an emotional problem often experienced in early childhood, especially when they first enter an educational environment. This condition can hinder the adaptation process, independence, and involvement of children in learning activities. Therefore, the role of teachers and parents is an important factor in helping children overcome separation anxiety. This study aims to describe the role of teachers and parents in overcoming SAD in early childhood at PAUD. This study uses a qualitative approach with a case study method because it allows researchers to explore in depth the behavior of children and the dynamics of interaction between children, teachers, and parents in a natural context. The research subject was one child at the Al-Hafidz Early Childhood Education Center in Cipocok Jaya, Serang City. Data collection techniques included observation, in-depth interviews, and documentation. The results of the study, based on observation and interviews, showed that the child experienced symptoms of SAD, such as crying when separated from parents, refusing to enter the classroom, and showing high emotional dependence. Teachers act as surrogate figures who provide a sense of security through play-based approaches, empathetic communication, and enjoyable learning strategies. Meanwhile, parents, especially mothers, play a role through permissive parenting patterns that influence the child's condition. Intensive collaboration between teachers and parents has a positive impact on improving the child's independence and adaptability